Struma ovarii: un cas rare de kyste ovarien géant - Raiteb, Hanane (Pan Afr Med J, 2017)
Struma ovarii is a rare tumor, which accounts for 2.7% of ovarian teratomas and 0.01% of ovarian tumors. It usually affects women in the fifth decades of life and is most often detected incidentally during ultrasound and then confirmed histologically. The gold standard treatment is surgery and prognosis is excellent. We here report the particular case of a young female patient with giant struma ovarii whose radiological features were classified as unusual presentation. We match patient's data with those from the literature.